LEARNING MEDIA FOR FAITH IN THE LAST DAY IN SURAH AN-NABA - Tanzilul Authar tanzil (Journal Informatic, Education and Management (JIEM), 2026)
The word "media" comes from Latin and is the plural form of the word "medium", which literally means "intermediary". Learning Media explains that media is something that transmits messages and can stimulate the thoughts, feelings and desires of the audience (students) so that it can encourage the learning process in themselves. The term learning media has several broad and narrow meanings. Media is a method formulated to optimize interaction between students and educators or between students and teachers in order to achieve effective and efficient learning goals. From the results of a simple analysis that the author carried out, it is clear that there are many patterns of application of faith learning media in the last days that the author found in Surah An-Naba'. Among them; (1) Discovery Learning; (2) learning media with a phenomenological approach; (3) As-Sual learning media or questions or questions media; (4) there is a scientific approach or scientific learning media; (5) Punishment media; and (6) reflective media.